The SES equity gap and the reform from modular to linear GCSE mathematics - Pinot De Moira, A; Meadows, M; Baird, J (Wiley, 2019)
This article addresses whether the introduction of end‐of‐course, linear General Certificate of Secondary Education (GCSE) examinations changed the socio‐economic equity gap in England. The GCSE is a national examination offered in a wide range of subjects and taken by almost the entire 16‐year‐old age cohort. Between the years 2007 and 2014, it underwent a number of reforms to both the underlying curriculum and the examination structure. At the beginning of the period, examinations were primarily modular in structure where the course was decomposed into discrete units tested in a staged manner. By 2014, all GCSE examinations were linear and the whole course content was tested simultaneously when study was complete. These structural changes and the curriculum reforms mean that the impact of modular and linear testing on the performance of students has been the focus of recent interest. Some educational commentators suggested that modular examinations are more suitable for lower‐performing students, including those with lower socio‐economic status (SES). This research has been conducted to monitor the socio‐economic equity gap in the light of the structural changes. It focuses on GCSE mathematics and concludes that, although there is still a clear gap in attainment between disadvantaged students and their peers, this gap does not seem to be exacerbated by the examination structure. In other words, the linearisation of GCSE mathematics is unlikely to have increased inequity between students of high and low SES.